Birth Defect: An Over view (Journal of Paediatric Surgeons of Bangladesh, 2015)
Birth defects are a leading cause of infant death, accounting for more than 1 of every 5 infant deaths. Every year more than 8.14 million children are born with a serious birth defect, due to genetic or environmental causes. In the low and middle income countries the burden of birth defects is much higher than in highincome countries. Birth defects may be due to chromosomal, single-gene or multifactorial causes. Environmental factors are responsible for 510% of total birth defects, and include nutritional deficiencies, infectious diseases, maternal medical conditions, teratogenic medications, alcohol, recreational drugs, and teratogenic pollutants. Birth defects can be diagnosed during pregnancy or after the baby is born, depending on the specific type of birth defect. Of course, many birth defects cannot be prevented; this is especially true of defects that have a genetic component. However, ultrasonography and maternal serum screening can be used to detect serious foetal anomalies, including neural tube defects and chromosomal disorders. Early detection and treatment of birth defects can help prevent stillbirth or physical and intellectual disabilities.J. Paediatr. Surg. Bangladesh 4(2): 58-66, 2013 (July)